Effect on oral pH changes and taste perception in 10–14-year-old children, after calcium fortification of a fruit juice - Franklin, S.; Masih, S.; Thomas, A. M. (European archives of paediatric dentistry, 2015)
Aim The aim was to determine the effect of calcium fortification of a commercially available mixed-fruit juice on oral pH changes and taste perception in a group of 10 to 14 year-old Indian children. Method A controlled, blinded, non-randomised clinical trial was adopted, consisting of a sample of 100 healthy children (DMFT <3; age 10–14 years), who were exposed to three test juices one by one [Group A: original fruit juice (control group); Group B: calcium-fortified fruit juice and Group C: calcium + vitamin D fortified fruit juice]. Oral pH, collection of saliva and plaque sampling was undertaken, before and after the juice exposure by each subject at 0, 1, 5, 15, 30 and 45 min. The respective pH was measured with a digital pH meter. For taste perception, a scoring system was used after exposure of the juices to the subjects in a blind manner. The statistical evaluation was done using one-way ANOVA for salivary and plaque pH and Kruskal–Wallis test for buffer capacity and taste perception. Results There was a smaller drop in salivary and plaque pH ( p < 0.5) and a significant reduction in perceived taste ( p < 0.001) by the subjects after calcium modification of fruit juice. Conclusion The calcium-modified mixed fruit juices was less acidogenic compared with the unfortified juice, and hence will be less cariogenic and erosive towards teeth.